Evaluasi Struktur Ruang Kota Berdasarkan Ketersediaan Sarana Permukiman di Kabupaten Rembang Provinsi Jawa Tengah - Hidayat, Taufiq; Evitasari, Sherly (Sekolah Tinggi Pertanahan Nasional, 2024)
The presence of development disparities among sub-districts poses a significant issue for Rembang Regency. This study aims to assess the development level of the city, determine the centrality index for each sub-district, analyze the needs for facilities and infrastructure, and evaluate the carrying capacity of settlements in Rembang Regency. The findings will serve as a reference for policy formulation in regional development. This research employs quantitative methods, utilizing data from the Central Statistics Agency. Results from the scalogram analysis and centrality index indicate notable disparities between sub-districts in Rembang Regency. The highest service center and centrality value are concentrated in the Rembang sub-district, which serves as the capital of Rembang Regency. This is attributable to the sub-district's role as the governmental and economic hub of the region. Furthermore, the analysis of facility needs underscores the importance of developing educational facilities to enhance education services across Rembang Regency, ensuring they are accessible to the entire community. The availability of land in Rembang Regency is deemed highly conducive to the development of settlement facilities, as the settlement capacity has not been exceeded. Keywords: Urban Spatial Structure, Residential Facilities, Urban Development Analysis Rembang Regency, Central Java Province. INTISARI Keberadaan disparitas pembangunan antar-kecamatan merupakan masalah signifikan bagi Kabupaten Rembang. Penelitian ini bertujuan menilai tingkat perkembangan kota, menentukan indeks sentralitas untuk setiap kecamatan, menganalisis kebutuhan fasilitas dan infrastruktur, serta mengevaluasi daya dukung permukiman di Kabupaten Rembang. Temuan ini akan menjadi acuan bagi perumusan kebijakan dalam pembangunan daerah. Penelitian ini menggunakan metode kuantitatif dengan memanfaatkan data dari Badan Pusat Statistik. Hasil dari analisis skalogram dan indeks sentralitas menunjukkan adanya disparitas yang signifikan antar kecamatan di Kabupaten Rembang. Nilai pusat pelayanan dan sentralitas tertinggi terkonsentrasi di Kecamatan Rembang, yang berfungsi sebagai ibu kota Kabupaten Rembang. Hal ini disebabkan oleh peran kecamatan tersebut sebagai pusat pemerintahan dan ekonomi di wilayah ini. Lebih lanjut, analisis kebutuhan fasilitas menekankan pentingnya pengembangan fasilitas pendidikan untuk meningkatkan layanan pendidikan di seluruh Kabupaten Rembang, memastikan aksesibilitasnya bagi seluruh masyarakat. Ketersediaan lahan di Kabupaten Rembang dianggap sangat mendukung pengembangan fasilitas permukiman, karena kapasitas permukiman belum terlampaui. Kata Kunci: Struktur Ruang Kota, Sarana Permukiman, Analisis Pembangunan Kota, Kabupaten Rembang, Provinsi Jawa Tengah.